Traditional Chinese medicine atomizer ceramic material and preparation method thereof
By optimizing the composition and preparation method of ceramic materials for TCM nebulizers, the problems of corrosion resistance and atomization quality of existing ceramic materials in TCM nebulizers have been solved, and the stability and drug release efficiency under high temperature and high humidity environments have been improved.
Patent Information
- Application Number
- CN202511183728.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-14
AI Technical Summary
Existing ceramic materials have problems such as insufficient corrosion resistance, degradation of active ingredients, poor structural stability, and poor atomization quality in traditional Chinese medicine nebulizers, making it difficult to adapt to the complex characteristics of traditional Chinese medicine preparations.
A composite material consisting of silicon carbide, diatomaceous earth, alumina powder, nanocellulose, and mesoporous SiO2 microspheres was developed. This composite material was combined with an Al2O3-TiO2 composite coating and surface modifiers of γ-methacryloyloxypropyltriethoxysilane and boric acid. Through segmented sintering and surface modification, the pore structure, thermal response characteristics, and wettability of the material were optimized.
Maintaining a stable pore structure under high temperature and high humidity conditions improves the adsorption capacity and atomization quality of the medicine, reduces the risk of thermal degradation of traditional Chinese medicine components, extends the service life of the equipment, and enhances safety.
Smart Images

Figure CN120943668A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of ceramic materials, specifically to a ceramic material for a traditional Chinese medicine nebulizer and its preparation method. Background Technology
[0002] Traditional Chinese medicine nebulization therapy is a medical approach that integrates traditional Chinese medicine theory with modern inhalation therapy technology. It uses nebulizers to transform Chinese herbal preparations into fine particles for patients to inhale, thereby treating respiratory diseases and other ailments. Currently, most nebulizers on the market are made of metal or plastic. However, these materials are prone to problems such as insufficient corrosion resistance, adsorption or degradation of active ingredients, and poor hygiene and safety when exposed to high temperatures and complex acidic or alkaline solutions, thus affecting drug release efficiency and equipment lifespan. In contrast, ceramic materials, due to their excellent high-temperature resistance, chemical stability, and biocompatibility, have become a highly promising material choice for medical nebulizers.
[0003] Despite the numerous advantages of ceramic materials, the types of ceramics currently used in nebulizers remain relatively limited, and their performance is insufficient to fully adapt to the complex characteristics of traditional Chinese medicine preparations. For example, traditional diatomaceous earth-based porous ceramics are prone to pore structure degradation under continuous high humidity and high heat conditions, resulting in a significant decrease in the drug adsorption capacity and affecting the nebulization quality. Simultaneously, some alumina powder-based ceramic materials exhibit uneven thermal conductivity, easily leading to localized overheating during nebulization, which in turn causes the deterioration of active ingredients in traditional Chinese medicine, such as herbal essential oils, weakening their therapeutic effects.
[0004] Although ceramic materials have potential advantages in the application of TCM nebulization, existing ceramic materials still have several shortcomings: First, traditional porous ceramics are prone to pore collapse under long-term humid and hot conditions, leading to decreased structural stability and insufficient drug adsorption and transfer capacity; second, some alumina-based ceramics exhibit uneven thermal conductivity during heating and nebulization, and localized overheating can damage heat-sensitive components in TCM, reducing efficacy; third, the surface wettability control of existing ceramics is insufficient. For TCM preparations containing certain volatile oils or fat-soluble components, problems such as drug accumulation on the surface, large droplet size, and uneven particle distribution often occur, making it difficult to achieve good nebulization quality and lung deposition efficiency. Therefore, there is an urgent need to develop a ceramic material and preparation method with superior performance in terms of humid and hot stability, heat conduction uniformity, and surface wettability to improve the effectiveness of TCM nebulization therapy and extend the service life of equipment. Summary of the Invention
[0005] The purpose of this invention is to provide a ceramic material and preparation method for a traditional Chinese medicine nebulizer, in order to address the technical problems raised in the background section above.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] On one hand, the present invention provides a ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage: 30-38 parts silicon carbide, 20-28 parts diatomaceous earth, 10-18 parts alumina powder, 5-10 parts pore-forming agent, 2-4 parts binder, and 1-2 parts surface modifier;
[0008] The silicon carbide is of the β-SiC crystal form with a particle size D. 50 The thickness is 50μm±20μm, and its surface is covered with an Al2O3-TiO2 composite coating, wherein the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1.
[0009] The pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres in a mass ratio of 1:(0.5-2), wherein the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 10–30 nm. 50 It is 50-100nm.
[0010] As a preferred technical solution, the adhesive is a mixture of inorganic and organic adhesives, wherein the inorganic adhesive is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic adhesive is polyvinyl alcohol.
[0011] As a preferred technical solution, the surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:(1-3), and the complex is dissolved in an ethanol-water mixed solvent.
[0012] As a preferred technical solution, the ceramic material further includes 1 to 3 parts of a dopant, wherein the dopant is yttrium oxide or zirconium oxide.
[0013] On the other hand, a method for preparing a ceramic material for a traditional Chinese medicine nebulizer, comprising the following steps:
[0014] S1. Raw material pretreatment: Silicon carbide, diatomaceous earth, alumina powder, and dopant are mixed in a certain proportion and ball-milled for 2-6 hours using a planetary ball mill at a speed of 200-400 rpm and a ball-to-material ratio of 5:1-10:1 to obtain a particle size D. 50 Mixed powders ≤75μm;
[0015] S2. Slurry preparation: The mixed powder obtained in step S1 is added to deionized water and mixed with pore-forming agent and binder at a stirring speed of 200-400 rpm to form a slurry with a solid content of 50%-60%.
[0016] S3. Cold isostatic pressing: After the slurry is injected into the mold, it is held under pressure of 80-150MPa for 5-15 minutes to form a preform;
[0017] S4. Segmented sintering:
[0018] First stage: Heat to 600-800℃ at a rate of 2-5℃ / min and hold for 2-4 hours to remove the pore-forming agent;
[0019] Second stage: Increase the temperature to 1200-1400℃ at a rate of 1-3℃ / min, and hold in an argon atmosphere for 1-3 hours to inhibit oxidation;
[0020] S5. Surface modification treatment: Immerse the sintered ceramic in a surface modifier solution for 1 to 5 hours, then clean and dry.
[0021] As a preferred technical solution, in step S2, the stirring time of the slurry is 30 to 90 minutes.
[0022] As a preferred technical solution, in step S4, during the argon-protected sintering process, the oxygen content is controlled to be no higher than 100 ppm.
[0023] As a preferred technical solution, the slurry is subjected to vacuum degassing treatment before being injected into the mold to improve the uniformity of the preform density.
[0024] As a preferred technical solution, in step S5, the temperature of the surface modifier solution is 60-80°C.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] 1. This invention introduces silicon carbide (β-SiC) composite with diatomaceous earth and alumina powder, and uses a composite pore-forming agent composed of nanocellulose and mesoporous SiO2 microspheres, so that the ceramic material can maintain a stable pore structure under high temperature and high humidity environment, thereby maintaining the long-term stability of liquid adsorption and atomization performance.
[0027] 2. Using β-SiC with controllable particle size as the dominant thermally conductive phase, and optimizing its thermal response characteristics by coating with Al2O3-TiO2 composite coating, the problem of uneven thermal conductivity of traditional alumina powder ceramics leading to local overheating is solved, reducing the risk of thermal degradation of the effective components of traditional Chinese medicine at high temperatures and maintaining its component stability.
[0028] 3. By modifying the ceramic surface with a composite of γ-methacryloxypropyltriethoxysilane and boric acid, the wettability of the ceramic surface can be effectively controlled. This allows for uniform spreading of traditional Chinese medicine preparations containing certain volatile oils or fat-soluble components, reducing the accumulation of the liquid on the surface. By controlling the wettability of the ceramic surface, uniform spreading of the liquid on the ceramic surface can be achieved, improving the uniformity of droplet distribution and the controllability of particle size.
[0029] 4. The segmented sintering process under argon atmosphere and subsequent surface modification treatment significantly improve the oxidation resistance and overall density of ceramic materials, reduce structural deterioration and chemical failure during use, extend the service life of atomizers, and enhance the safety and reliability of equipment. Attached Figure Description
[0030] Figure 1 This is a flowchart illustrating the preparation method of the ceramic material for the traditional Chinese medicine nebulizer of the present invention. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Example 1
[0033] A ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage:
[0034] The mixture contains 34 parts silicon carbide, 24 parts diatomaceous earth, 15 parts alumina powder, 8 parts pore-forming agent, 3 parts binder, 1.5 parts surface modifier, and 2 parts dopant.
[0035] Among them, silicon carbide is of the β-SiC crystal form, with a particle size D 50 The particle size is 50μm±20μm, and its surface is coated with an Al2O3-TiO2 composite coating, in which the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1; the pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres, and the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 20 nm. 50 The wavelength is 80 nm, and the mass ratio of the two is 1:1; the binder is a mixture of inorganic and organic binders, wherein the inorganic binder is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic binder is polyvinyl alcohol; the surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:2, the complex is dissolved in an ethanol-water mixed solvent, and the dopant is yttrium oxide or zirconium oxide.
[0036] The preparation method of ceramic materials for traditional Chinese medicine nebulizers includes the following steps:
[0037] Step S1, Raw material pretreatment:
[0038] Silicon carbide, diatomaceous earth, alumina powder, and dopants were mixed in a specific ratio and fed into a planetary ball mill. Zirconia balls were added as grinding media, with a ball-to-material mass ratio of 8:1. The milling speed was set to 300 rpm, and the milling time was 4 hours to obtain a particle size D. 50 Mixed powder with a particle size of ≤75μm ensures uniform distribution of all components.
[0039] Step S2, Slurry preparation:
[0040] Add a pore-forming agent and a binder to the mixed powder obtained in step S1, add deionized water to adjust the slurry solid content to 55%, stir at 300 rpm for 30 minutes to obtain a uniformly dispersed slurry, and place the slurry under vacuum to degas in order to remove the mixed air bubbles and improve the uniformity of subsequent molding density.
[0041] Step S3, cold isostatic pressing:
[0042] After degassing, the slurry is injected into the mold and placed in a cold isostatic pressing device. It is held under pressure of 120MPa for 10 minutes, and after demolding, a uniformly structured preform is formed.
[0043] Step S4, Segmented sintering treatment:
[0044] The preform was placed in an atmosphere furnace for two-stage segmented sintering:
[0045] First stage: Heat to 700℃ at a rate of 3℃ / min and hold for 3 hours to fully remove the pore-forming agent;
[0046] Second stage: Continue to heat to 1300℃ at a rate of 2℃ / min, and keep at this temperature for 2 hours in an argon atmosphere (oxygen content ≤100ppm) to inhibit oxidation.
[0047] Step S5, Surface modification treatment:
[0048] The sintered ceramic sample was immersed in a surface modifier solution (a composite solution of γ-methacryloyloxypropyltriethoxysilane and boric acid in a ratio of 1:2) at a temperature of 70°C for 2 hours. After treatment, it was rinsed with deionized water and dried at 60°C for 6 hours.
[0049] The obtained ceramic material was tested, and its performance results are as follows: porosity of 31.2%, ensuring excellent gas permeability; liquid adsorption capacity of 32.5 mg / g, indicating strong surface adsorption capacity; flexural strength reaching 48.7 MPa, demonstrating good structural stability; and air permeability resistance controlled at 4.8 kPa·s / m. 3 Suitable for atomized airflow.
[0050] The formulation in this embodiment uses a medium proportion of silicon carbide, diatomaceous earth, and alumina powder. After two-stage sintering and modification, the resulting ceramic material has good comprehensive performance and is a recommended preferred solution.
[0051] Example 2
[0052] A ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage:
[0053] 30 parts silicon carbide, 20 parts diatomaceous earth, 18 parts alumina powder, 10 parts pore-forming agent, 4 parts binder, 2 parts surface modifier and 2 parts dopant.
[0054] Among them, silicon carbide is of the β-SiC crystal form, with a particle size D 50 The particle size is 50μm±20μm, and its surface is coated with an Al2O3-TiO2 composite coating, in which the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1; the pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres, and the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 20 nm. 50 The wavelength is 80 nm, and the two are compounded in a mass ratio of 1:1; the binder is a mixture of inorganic binder and organic binder, wherein the inorganic binder is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic binder is polyvinyl alcohol; the surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:3, the complex is dissolved in an ethanol-water mixed solvent, and the dopant is yttrium oxide or zirconium oxide.
[0055] The preparation method of the ceramic material for the TCM atomizer is the same as in Example 1.
[0056] The obtained ceramic material was tested, and its performance results are as follows: the porosity increased to 38.6%, which is beneficial for liquid adsorption; the liquid adsorption capacity increased to 38.0 mg / g, the highest among the five groups; the flexural strength decreased to 40.3 MPa; and the air permeability resistance increased slightly to 6.1 kPa·s / m. 3 However, it is still within an acceptable range.
[0057] This embodiment uses the lower or upper limits of each component ratio (e.g., 30 wt% silicon carbide, 20 wt% diatomaceous earth, 18 wt% alumina powder, 2 wt% modifier, etc.) to verify the end-point performance of the component range described in the claims. The lower limit ratio is suitable for scenarios that emphasize drug release performance, but the strength is slightly sacrificed, making it suitable for auxiliary drug-loaded ceramics.
[0058] Example 3
[0059] A ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage:
[0060] The mixture contains 38 parts silicon carbide, 28 parts diatomaceous earth, 10 parts alumina powder, 5 parts pore-forming agent, 2 parts binder, 1 part surface modifier, and 3 parts dopant.
[0061] Among them, silicon carbide is of the β-SiC crystal form, with a particle size D 50 The particle size is 50μm±20μm, and its surface is coated with an Al2O3-TiO2 composite coating, in which the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1; the pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres, and the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 20 nm. 50 The wavelength is 80 nm, and the two are compounded in a mass ratio of 1:1; the binder is a mixture of inorganic binder and organic binder, wherein the inorganic binder is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic binder is polyvinyl alcohol; the surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:1, the complex is dissolved in an ethanol-water mixed solvent, and the dopant is yttrium oxide or zirconium oxide.
[0062] The preparation method of the ceramic material for the TCM atomizer is the same as in Example 1.
[0063] The obtained ceramic material was tested, and its performance results are as follows: porosity decreased to 26.1%, resulting in high density; flexural strength increased to 53.9 MPa; liquid adsorption capacity decreased to 27.4 mg / g; and air permeability resistance was low, only 3.5 kPa·s / m. 3 .
[0064] This embodiment uses the maximum silicon carbide content (38wt%) and the maximum diatomite content (28wt%) to explore the effect of dense structure on performance. This formula has excellent strength and is suitable for structural support or TCM nebulization devices with high pressure requirements, but its drug loading and air permeability are slightly weak.
[0065] Example 4
[0066] A ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage:
[0067] The ingredients are: 33 parts silicon carbide, 25 parts diatomaceous earth, 15 parts alumina powder, 8 parts pore-forming agent, 3 parts binder, 2 parts surface modifier, and 2 parts dopant.
[0068] Among them, silicon carbide is of the β-SiC crystal form, with a particle size D 50The particle size is 50μm±20μm, and its surface is coated with an Al2O3-TiO2 composite coating, in which the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1; the pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres, and the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 20 nm. 50 The wavelength is 80 nm, and the two are compounded in a mass ratio of 1:2; the binder is a mixture of inorganic binder and organic binder, wherein the inorganic binder is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic binder is polyvinyl alcohol; the surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:2, the complex is dissolved in an ethanol-water mixed solvent, and the dopant is yttrium oxide or zirconium oxide.
[0069] The preparation method of the ceramic material for the TCM atomizer is the same as in Example 1.
[0070] The obtained ceramic material was tested, and its performance results are as follows: porosity reaches 35.4%, which is beneficial for air permeability and liquid adsorption; liquid adsorption capacity is 35.8 mg / g; flexural strength is 46.2 MPa; and air permeability resistance is 4.2 kPa·s / m. 3 .
[0071] This embodiment focuses on optimizing the structure and ratio of the pore-forming agent (nanocellulose: mesoporous SiO2 microspheres = 1:2) and γ-methacryloyloxypropyltriethoxysilane: boric acid = 1:2, emphasizing the balance between pore structure regulation and surface functionalization. A better balance is achieved among indicators such as strength, permeability, and drug loading, demonstrating the importance of structural regulation and optimized surface modifier ratios.
[0072] Comparative Example 1 (out of range)
[0073] A ceramic material for a traditional Chinese medicine nebulizer, comprising the following components by mass percentage:
[0074] The mixture contains 40 parts silicon carbide, 24 parts diatomaceous earth, 15 parts alumina powder, 8 parts pore-forming agent, 3 parts binder, and 1.5 parts surface modifier, without any dopants.
[0075] Among them, silicon carbide is of the β-SiC crystal form, with a particle size D 50 The particle size is 50μm±20μm, and its surface is coated with an Al2O3-TiO2 composite coating, in which the mass ratio of Al2O3 to TiO2 in the composite coating is 3:1; the pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres, and the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 20 nm. 50The sample has a wavelength of 80 nm and is compounded with the other two components at a mass ratio of 1:1. The binder is a mixture of inorganic and organic binders. The inorganic binder is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic binder is polyvinyl alcohol. The surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, with a mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid of 1:2. The complex is dissolved in an ethanol-water mixed solvent.
[0076] The preparation method of a ceramic material for a traditional Chinese medicine atomizer is similar to that of Example 1, except that no dopant is added during the preparation process.
[0077] The obtained ceramic material was tested, and its performance results are as follows: the porosity is only 20.3%, making it difficult for gas to pass through; the liquid adsorption capacity is significantly reduced to only 22.0 mg / g; and the air permeability resistance increases to 7.9 kPa·s / m. 3 The flexural strength decreased to 35.0 MPa.
[0078] In this embodiment, the silicon carbide content exceeds the upper limit of the claims (40 wt%), and the diatomaceous earth content is below the lower limit (18 wt%), thus serving as a comparative example. When the component proportions exceed the range specified in the claims, the overall performance of the ceramic material significantly decreases, verifying the rationality and necessity of the scope defined in the claims.
[0079] The following table summarizes the technical effects of each embodiment and comparative example:
[0080]
[0081] As can be seen from the above embodiments, changes in the proportions of each component significantly affect the pore structure, drug loading capacity, and mechanical properties of the ceramic material. Specifically, increasing the silicon carbide content helps improve strength, but decreases porosity and drug loading. The proportion and type of pore-forming agent have a significant effect on regulating the pore structure. A ratio of γ-methacryloyloxypropyltriethoxysilane to boric acid within the range of 1:1 to 1:3 can enhance surface activity, thereby improving drug loading capacity. When the components exceed the scope defined in the claims, the overall performance of the material decreases, indicating that the defined scope is reasonable and necessary.
[0082] In summary, this invention demonstrates excellent synergistic effects in terms of raw material component ratio, pore structure control, and surface modification optimization. The resulting ceramic material for TCM nebulizers achieves an optimized balance between air permeability, drug carrying capacity, and structural strength, exhibiting significant technological advancement and application value.
[0083] The above embodiments are only used to illustrate the technical methods of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical methods of the present invention without departing from the spirit and scope of the technical methods of the present invention.
Claims
1. A ceramic material for a traditional Chinese medicine nebulizer, characterized in that, It includes the following components by weight percentage: 30-38 parts silicon carbide, 20-28 parts diatomaceous earth, 10-18 parts alumina powder, 5-10 parts pore-forming agent, 2-4 parts binder, and 1-2 parts surface modifier; The silicon carbide is of the β-SiC crystal form with a particle size D. 50 The thickness is 50μm±20μm, and its surface is covered with an Al2O3-TiO2 composite coating, wherein the mass ratio of Al2O3 to TiO2 in the composite coating is 3:
1. The pore-forming agent is composed of nanocellulose and mesoporous SiO2 microspheres in a mass ratio of 1:(0.5-2), wherein the particle size D of the nanocellulose is... 50 The particle size D of the mesoporous SiO2 microspheres is 10–30 nm. 50 It is 50-100nm.
2. The ceramic material for the traditional Chinese medicine nebulizer according to claim 1, characterized in that, The adhesive is a mixture of inorganic and organic adhesives, wherein the inorganic adhesive is one or a combination of montmorillonite and aluminum dihydrogen phosphate, and the organic adhesive is polyvinyl alcohol.
3. The ceramic material for the traditional Chinese medicine nebulizer according to claim 1, characterized in that, The surface modifier is a complex of γ-methacryloxypropyltriethoxysilane and boric acid, wherein the mass ratio of γ-methacryloxypropyltriethoxysilane to boric acid is 1:(1-3), and the complex is dissolved in an ethanol-water mixed solvent.
4. The ceramic material for the traditional Chinese medicine nebulizer according to claim 1, characterized in that, The ceramic material also includes 1 to 3 parts of a dopant, wherein the dopant is yttrium oxide or zirconium oxide.
5. A method for preparing ceramic material for a traditional Chinese medicine nebulizer, characterized in that, Includes the following steps: S1. Raw material pretreatment: Silicon carbide, diatomaceous earth, alumina powder, and dopant are mixed in a certain proportion and ball-milled for 2-6 hours using a planetary ball mill at a speed of 200-400 rpm and a ball-to-material ratio of 5:1-10:1 to obtain a particle size D. 50 Mixed powders ≤75μm; S2. Slurry preparation: The mixed powder obtained in step S1 is added to deionized water and mixed with pore-forming agent and binder at a stirring speed of 200-400 rpm to form a slurry with a solid content of 50%-60%. S3. Cold isostatic pressing: After the slurry is injected into the mold, it is held under pressure of 80-150MPa for 5-15 minutes to form a preform; S4. Segmented sintering: First stage: Heat to 600-800℃ at a rate of 2-5℃ / min and hold for 2-4 hours to remove the pore-forming agent; Second stage: Increase the temperature to 1200-1400℃ at a rate of 1-3℃ / min, and hold in an argon atmosphere for 1-3 hours to inhibit oxidation; S5. Surface modification treatment: Immerse the sintered ceramic in a surface modifier solution for 1 to 5 hours, then clean and dry.
6. The preparation method according to claim 5, characterized in that, In step S2, the stirring time of the slurry is 30 to 90 minutes.
7. The preparation method according to claim 5, characterized in that, In step S4, during the argon-protected sintering process, the oxygen content is controlled to be no higher than 100 ppm.
8. The preparation method according to claim 5, characterized in that, The slurry is vacuum degassing before being injected into the mold to improve the uniformity of the preform density.
9. The preparation method according to claim 5, characterized in that, In step S5, the temperature of the surface modifier solution is 60–80°C.